Small scale farm mechanization catalogue: Clearinghouse technical report series 015 - Technologies for African Agricultural Transformation (Technologies for African Agricultural Transformation, 2022)
Small-scale mechanization is the key to reducing drudgery and increasing productivity among African farmers. For too long farming in Africa is regarded as a path to poverty rather than a profitable agribusiness. This is due in large part for dependency upon tedious hand labor, poor returns to effort and lack of investment into farming systems. A wide range of small-scale equipment is available to improve returns to labor and change this poor image of farming. This equipment include tillers, power weeders, power sprayers, soil augers, irrigation systems, multi-crop threshers and a host of other equipment that are becoming commercially available for the first time. Profitable use of these equipment is not guaranteed because their use requires new skillsets, rigorous maintenance, and safety precautions. At the same time, expanded reliance upon this equipment provides economic opportunity through their distribution and service provision. This catalogue provides insight into this useful farming equipment.